A comparison of physical fitness in patients with bipolar disorder, schizophrenia and healthy controls. Issue 20 (24th September 2016) - Vancampfort, Davy; Stubbs, Brendon; Sienaert, Pascal; Wyckaert, Sabine; De Hert, Marc; Soundy, Andrew; Probst, Michel
Abstract: Purpose: To compare the physical fitness of inpatients with bipolar disorder, schizophrenia and healthy controls. Method: Twenty-two inpatients with bipolar disorder, and 22 age-, gender- and body mass index-matched inpatients with schizophrenia and healthy controls were included. All participants performed the Eurofit test battery and the International Physical Activity Questionnaire. One way analyses of variance with post hoc Scheffe were applied to examine differences. Results: Both patient groups were significantly more physically inactive and had a significantly impaired speed of limb movement, explosive muscle strength and abdominal muscular endurance compared to the healthy controls. No significant differences between the patient groups were found. Conclusions: The results suggest that physical fitness and physical activity participation are similar among inpatients with bipolar disorder and schizophrenia but markedly lower than healthy controls. Chronic inpatients with lower levels of physical activity may particularly benefit from rehabilitation interventions aimed at increasing physical fitness. Implications for Rehabilitation: Physical fitness should receive similar attention in the treatment of bipolar disorder and schizophrenia. Sedentary patients with a longer duration of illness need additional support in changing lifestyle behaviours. Rehabilitation should not only consider cardio-respiratory fitness but also muscular endurance, muscular strength and balance.